Compatible traits of oleaginous Mucoromycota fungi for lignocellulose-based simultaneous saccharification and fermentation - Cristian Bolaño Losada; Ondrej Slaný; Dana Byrtusová; Boris Zimmermann; Svein Jarle Horn; Achim Kohler; Volha Shapaval (Biotechnology for Biofuels and Bioproducts)
Abstract Background Mucoromycota fungi are promising for the production of second-generation biofuel from single-cell oils (SCOs) using lignocellulose biomass. Despite the lack of enzymatic capability for efficiently degrading lignocellulose in Mucoromycota fungi, simultaneous saccharification and fermentation (SSF) offers an attractive solution by combining enzymatic hydrolysis and fermentation in the same procedure. This study explored specific traits of various Mucoromycota species to evaluate their suitability for SSF, due to the frequent and significant gap between the microorganism and enzyme optimal conditions. Results The suitability of nine oleaginous fungal strains from the Mucoromycota phylum for use in lignocellulose-based simultaneous saccharification and fermentation was evaluated. Several traits, such as thermal tolerance, biochemical composition changes in response to incubation temperature, cellobiose and cellulose response and induction of β-glucosidase and endoglucanase, were evaluated. Lichtheimia corymbifera was the most suitable species for SSF due to its ability to grow up to 45 °C, with a consequent decrease in lipid unsaturation, and good uptake of cellobiose with induction of β-glucosidase and endoglucanase expression. The Cunninghamella blackesleeana and Mucor circinelloides strains were also considered good candidates; despite the cultivation should not exceed 35 °C, their good uptake of cellobiose and the expression of extracellular β-glucosidase induced by cellobiose indicated that they could increase the enzymatic hydrolysis efficiency. C. blakesleeana outperformed all the other tested strains in terms of β-glucosidase activity expression. In addition, both endoglucanase and β-glucosidase activities of Rhizopus stolonifer and M. circinelloides were induced by cellobiose. Mortierella alpina and Mortierella hyalina were not considered suitable for simultaneous saccharification and fermentation due to their reduced tolerance to high temperatures and poor response to cellobiose utilization. Conclusions This study identified beneficial traits of Mucoromycota species for simultaneous saccharification and fermentation using lignocellulose, contributing to an optimal selection for producing lipid-derived second-generation biofuels.